Los Creoles de la costa Caribe de Nicaragua: entre la subalternidad y la hegemonía. - Herra Monge, Mayra (2012)
This article presents the Creoles that inhabit the South Atlantic Autonomous Region of Nicaragua, their origins and the construction of their identity, in contrast with the other ethnic groups living in this same territory. Firstly, it provides general data about the Atlantic or Caribbean Coast of Nicaragua, following with a description of the process of negotiation of the Creole identity, and their oscillation between subalternity and hegemony, from their ethnogenesis to the present times.